CCNA ICND 2004 - Odom, Wendell (Cisco Press, 2011)
This book is designed to provide information about selected topics for the ICND Exam for the CCNA certification. Every effort has been made to make this book as complete and accurate as possible, but no warranty or fitness is implied. The information is provided on an "as is" basis. The author, Cisco Press, and Cisco Systems, Inc. shall have neither liability nor responsibility to any person or entity with respect to any loss or damages arising from the information contained in this book or from the use of the discs or programs that may accompany it. The opinions expressed in this book belong to the author and are not necessarily those of Cisco Systems, Inc. Feedback Information At Cisco Press, our goal is to create in-depth technical books of the highest quality and value. Each book is crafted with care and precision, undergoing rigorous development that involves the unique expertise of members of the professional technical community. Reader feedback is a natural continuation of this process. If you have any comments regarding how we could improve the the quality of this book, or otherwise alter it to better suit your needs, you can contact us through e-mail at feedback@ciscopress.com. Please be sure to include the book's title and ISBN in your message. We greatly appreciate your assistance. Trademark Acknowledgments All terms mentioned in this book that are known to be trademarks or service marks have been appropriately capitalized. Cisco Press or the Cisco Systems, Inc. cannot attest to the accuracy of this information. Use of a term in this book should not be regarded as affecting the validity of any trademark or service mark.